Multiwall carbon nanotubes filled with Al4C3: Spectroscopic signatures for electron-phonon coupling due to doping process. (November 2017) - Araujo, P.T.; Barbosa Neto, N.M.; Sousa, M.E.S.; Angélica, R.S.; Simões, S.; Vieira, M.F.G.; Dresselhaus, M.S.; Leite dos Reis, M.A.
Abstract: The spectroscopic signatures related to doping mechanisms in multiwall carbon nanotubes filled with aluminum carbide (Al 4 C 3 @MWCNTs) were studied and interpreted relative to changes in their electronic and phononic structures. Unfilled MWCNTs were used as standard samples to help interpreting the filling and the doping processes. The samples were characterized via scanning electron microscopy, transmission electron microscopy, X-ray diffraction and resonant Raman spectroscopy. The electron-phonon coupling mechanisms associated to the Raman intensities, frequencies and linewidths of the G- and G'-band Raman modes were analyzed and connected to the doping mechanism in these multi-walled systems. Our results indicate that the Al4 C3 particles transfer electrons to the MWCNTs. In order to shed light into the experimental findings, theoretical calculations were performed using two examples of filled and unfilled achiral MWCNTs and the results for the density of electronic states indicate that the two systems under consideration, exhibit metallic behavior, with aluminum carbide doping the carbon nanotubes, thereby supporting our experimental observations. Graphical abstract: